Study on growth traits at weaning and yearling stages of indigenous and F1 crossbred buffalo in Bangladesh (Asian Journal of Medical and Biological Research, 2018)
This study was planned to clarify the variation of body weight and average daily gain traits in both indigenous and F1 crossbreed (Local×Mediterranean) buffalo at weaning (sixth month) and yearling stages (twelfth month). Data were collected from 33 indigenous and 35 F1 crossbred buffalo progeny during the period of 2011 to 2014 with intensive management system at Research and Development farm of Lal Teer Livestock Limited in Bangladesh. The gathered data were analyzed using general linear model (GLM) and independent sample t test. The effect of parity, sex, season and breeding year on body weight and average daily gain were observed where significant values found in breeding period (p